Isothiocyanates, Nitriles, and Epithionitriles from Glucosinolates Are Affected by Genotype and Developmental Stage in Brassica oleracea Varieties - Hanschen, Franziska S.; Schreiner, Monika (Frontiers in Plant Science, 2017)
Vegetables of the Brassica oleracea group, such as broccoli, cauliflower, and cabbage, play an important role for glucosinolate consumption in the human diet. Upon maceration of the vegetable tissue, glucosinolates are degraded enzymatically to form volatile isothiocyanates, nitriles and epithionitriles. However, only the uptake of isothiocyanates is linked to the cancer preventive effects. Thus, it is of great interest to evaluate especially the isothiocyanate formation. Here, we studied the formation of glucosinolates and their respective hydrolysis products in sprouts and fully developed vegetable heads of different genotype of the five B. oleracea varieties: broccoli, cauliflower as well as white, red, and savoy cabbages. Further, the effect of ontogeny (developmental stages) during the head development on the formation glucosinolates and their respective hydrolysis products was evaluated at three different developmental stages (mini, fully developed and over-mature head). Broccoli and red cabbage were mainly rich in 4-(methylsulfinyl)butyl glucosinolate (glucoraphanin), whereas cauliflower, savoy cabbage and white cabbage contained mainly 2-propenyl (sinigrin) and 3-(methylsulfinyl)propyl glucosinolate (glucoiberin). Upon hydrolysis, epithionitriles or nitriles were often observed to be the main hydrolysis products, with 1-cyano-2,3-epithiopropane being most abundant with up to 5.7 µmol/g FW in white cabbage sprouts. Notably, sprouts often contained more than 10 times more glucosinolates or their hydrolysis products compared to fully developed vegetables. Moreover, during head development, both glucosinolate concentrations as well as hydrolysis product concentrations changed and mini heads contained the highest isothiocyanate concentrations. Thus, from a cancer preventive point of view, consumption of mini heads of the B. oleracea varieties is recommended.